Aggression Profiles in the Spanish Child Population: Differences in Perfectionism, School Refusal and Affect - Vicent, María; Inglés, Cándido J.; Sanmartín, Ricardo; Gonzálvez, Carolina; García-Fernández, José Manuel (Frontiers in Behavioral Neuroscience, 2018)
The aim of this study was to identify the existence of combinations of aggression components (Anger, Hostility, Physical Aggression and Verbal Aggression) that result in different profiles of aggressive behavior in children, as well as to test the differences between these profiles in scores of perfectionism, school refusal and affect. It is interesting to analyze these variables given: (a) their clinical relevance due to their close relationship with the overall psychopathology, and (b) the need for further evidence regarding how they are associated with aggressive behavior. The sample consisted of 1202 Spanish primary education students between the ages of 8 and 12. Three aggressive behavior profiles for children were identified using Latent Class Analysis: High Aggression (Z scores between .69 and .7), Moderate Aggression (Z scores between -.39 and -.47) and Low Aggression (Z scores between -1.36 and -1.58). These profiles were found for 49.08 %, 38.46 % and 12.48 % of the sample, respectively. High Aggression scored significantly higher than Moderate Aggression and Low Aggression on Socially Prescribed Perfectionism, Self-Oriented Perfectionism, the first three factors of school refusal (i.e. FI. Negative Affective, FII. Social Aversion and/or Evaluation, FIII. To Pursue Attention), and Negative Affect. In addition, Moderate Aggression also reported significantly higher scores than Low Aggression for the three first factors of school refusal and Negative Affect. Conversely, Low Aggression had significantly higher mean scores than High Aggression and Moderate Aggression on Positive Affect. Results demonstrate that High Aggression was the most maladaptive profile having a high risk of psychological vulnerability. Aggression prevention programs should be sure to include strategies to overcome psychological problems that characterize children manifesting high levels of aggressive behavior.